A transitivity analysis of medical brochures with a focus on cervical and breast cancer / Sakila Govindaraju - Govindaraju, Sakila (2014)
This study analyzed four medical brochures consisting of Cervical Cancer and Breast Cancer. Medical brochures were chosen because they are important non-verbal tools that are used for creating awareness to the public about diseases. The study aimed to explore the transitivity choices used in medical brochures as well as the role of transitivity in creating meaning. The theory of Systemic Functional Linguistics by Hallidayan’s and Matthiessen’s (2004) is the theoretical framework of this study. The study also looked at Halliday (1994), Eggins’s (2004) Thompson (2004), Bloor and Bloor (2004) and Martin et al (1997) System of Transitivity. This study confines itself to the written text hence, pictures and diagrams are not a part of this study. The findings reveal the predominantly used Process types in this study are Material processes (54%) and Relational processes (33%). The high usages of Material processes are due to general procedures that are included in these brochures and the Relational processes to give descriptions of diseases. Followed by other process types such as Mental processes (6%), Behavioural processes (1%), Verbal processes(4%) and Existential processes(2%). All these processes are insignificantly used in these brochures. The predominantly used Circumstantial elements are Circumstance of Location (41%), Circumstance of Manner (25%) and Circumstance of Extent (18%). Meanwhile other Circumstantial elements were least used in medical brochures. The use of proper choices of process types and sentence structures will present the information effectively. The findings obtained will be helpful in teaching, designing and producing brochures. Future research can be looking at interpersonal accepts and multimodality analysis for the pictures and diagrams.